A Multicenter Prospective Survey of Adverse Events Associated with Acupuncture and Moxibustion in Japan - Furuse, Nobutatsu (Med Acupunct, 2017)
Background: There have been only a few prospective surveys on adverse events (AEs) in Japanese-style acupuncture practice, and these surveys were conducted only in a single college acupuncture clinic. Objective: The goal of this research was to assess the safety of acupuncture and moxibustion performed in educational facilities in Japan. Materials and Methods: This was a multicenter prospective survey, using paper reporting forms. It was conducted in eight acupuncture clinics affiliated with educational institutions. The subjects were outpatients attending the clinics. The main outcome measure was the number of reported adverse events. The study was conducted for 5–7 months at each facility between October 2014 and June 2015. Participating acupuncture practitioners were instructed to self-report AEs observed during and after treatment; patients were interviewed upon treatment completion. For returning patients, treatment was preceded by an interview survey regarding the AEs identified after the previous treatment session. A specialized 4-sheet questionnaire was used. Results: Two hundred and thirty-two acupuncture practitioners participated, 2180 patients received treatment, and there were 14,039 sessions, overall. In total, 847 (6.03%) AEs were reported. The most common AEs included subcutaneous bleeding and hematomas (370, 2.64%), followed by discomfort (109, 0.78%) and residual pain at insertion points (94, 0.67%). No infections or serious AEs were reported. Conclusions: Acupuncture and moxibustion performed in educational facilities in Japan were safe because most of the AEs reported were mild and transient. However, the risk cannot be defined definitely because the survey sample size was too small.